PENGARUH PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Marisa, Meira; Zulkifli, Zulkifli; Nurhasanah, Nurhasanah (Gapenas Publisher, 2023)
The study's goal is to put a dollar amount on the effect that municipal taxes and levies have on the per capita income (PDI) of South Sumatra's several municipalities. In addition, regional penalties and regional taxes will be studied alongside the PAD of each city and regency in South Sumatra Province. The Regional Government Financial Statements of 17 (seventeen) Regency/Cities in South Sumatra for the 2017-2021 Fiscal Year were the major data source for this study. These statements were released by the Supreme Audit Agency of the Republic of Indonesia (BPKRI). Multiple linear regression was used in IBM SPSS 25 to examine the data from this study. In South Sumatra, regional taxes seem to have a little impact on regional revenue (Sig. 0.000 0.05), but regional retribution has no effect on regency/city regional original income (Sig. 0,221 > 0.05). Multiple experiments showed that the results of regional taxes and regional levies had a significant impact on regency/city original revenue in South Sumatra, with Sig values ranging from 0.000 to 0.05